Inhibition of protease activity and anti‐quorum sensing of the potential fraction of ethanolic extract from Sansevieria trifasciata Prain leaves against Pseudomonas aeruginosa - Laurentius Hartanto Nugroho; Endah Retnaningrum; Yekti Asih Purwestri; Whika Febria Dewatisari (Indonesian Journal of Biotechnology, 2023)
Sansevieria trifasciata is a plant that is commonly utilized in traditional medicine. The leaves of S. trifasciata show antibacterial properties against Pseudomonas aeruginosa. This bacterium is an opportunistic pathogen that can cause serious illness in humans and produce a variety of virulence factors responsible for bacterial pathogenesis with quorum sensing (QS) systems that mediate intracellular communication. Bacteria produce protease through a QS mechanism in which they express signaling molecules to become pathogens. Proteases are extracellular enzymes required for successful infection that mediate biofilm spread through QS and regulate a variety of cellular and physiological functions. This research aimed to evaluate the protease, and anti‐QS activities of the ethanolic extract from S. trifasciata leaves against P. aeruginosa and the expression of QS genes. An azocasein test was used to determine the protease activity in qualitative and quantitative methods. Using real‐time quantitative polymerase chain reaction, a study was conducted to investigate the effect of ethanolic extract from S. trifasciata leaves on selected QS‐regulatory genes at the transcriptional level. The results showed that the potential ethanolic extract from S. trifasciata leaves inhibited the protease enzyme activity by as much as 77.1%. The potential ethanolic extract from S. trifasciata leaves decreased the expressions of lasA, lasB, lasI, lasR, rhlI, and rhlR with 2‐ΔΔCt values of 0.81, 0.93, 0.76, 0.97, 0.90, and 0.55 respectively.